SPECIFIC FEATURES OF DYSARTHRIA SPEECH DISORDER IN CHILDREN WITH SPEECH DEFICIENCY - Makhmudova Madinakhan; Khasanova Iroda (Journals Park Publishing, 2023)
This article describes the specific features of dysarthric speech disorder, its forms, symptoms and mechanisms of manifestation, and it can be seen that Tardien divides the speech deficits of dysarthric children into 4 levels.
Keywords: Dysarthria, anarthria, phonemic hearing, speech deficiency, sound pronunciation, grammatical disorder, vocabulary, articulation, motor skills.